Couples in breast cancer survivorship: Daily associations in relationship satisfaction, stress, and health - M. Rosie Shrout; Megan E. Renna; MiKaila J. Leonard; Elliot M. Friedman; Kathy D. Miller (Comprehensive Psychoneuroendocrinology)
Romantic relationships are a key health determinant underlying both morbidity and mortality. Dr. Janice Kiecolt-Glaser’s prolific research revealed cardiovascular, metabolic, endocrine, and immune pathways connecting marriage to health and longevity. In addition to her empirical work, she developed conceptual models on marriage, the gut microbiome, stress reactivity, and spousal health concordance; these models guide and inspire mechanistic research, serve as essential readings for graduate students and mentees, and provide inspiration for researchers across career stages. This paper highlights Dr. Kiecolt-Glaser’s influential work, includes personal reflections and professional growth as past mentees, and provides Dr. Kiecolt-Glaser-inspired evidence linking relationships to health among couples in breast cancer survivorship. Using baseline questionnaires and daily dairies, breast cancer survivors (stage I-IIIB) and their cohabiting partners (60 individuals, 30 couples) rated their relationship satisfaction, stress, and physical health symptoms every day for 7 days. Results suggest that breast cancer survivors and their partners who felt more satisfied with their relationships also felt less stressed, both typically and on a daily basis. Survivors’ and partners’ lower stress was also associated with fewer physical health problems on average and in daily life. These findings demonstrate the daily stress and health advantages of satisfying relationships for both breast cancer survivors and their partners. We discuss the study’s implications and several avenues for Dr. Kiecolt-Glaser-inspired research addressing a relationship’s long-term health impact among couples in survivorship.